Effects of strategy, competition, decentralizationand organizational capabilities on firm performance:The mediating role of strategic management accounting / Tan Ah Lay - Tan, Ah Lay (2014)

(untitled)
Traditional management accounting‟s lack of strategic orientation has mooted much debates and research interest on strategic management accounting (SMA) since the late 1980s. Even though there is no agreed framework, academics have recommended many SMA techniques which they claim to be external and long term focused, and able to assist managers in strategic decision-making process. But “SMA or SMA techniques have not been adopted widely, nor is the term widely used” (Langfield-Smith, 2008) and there seems to be a gap between SMA literature and strategic management literature (Nixon and Burns, 2012). SMA research has ignored resource-based view of the firm emphasized in strategic management. Using a survey on management accountants from 103 manufacturing strategic business units of listed companies in Malaysia, this research investigates the relationship between competitive strategies identified by Porter (1980) and SMA. The contingency model which incorporates the two dimensions of SMA, i.e. strategic role of accountant and SMA usage, also assesses the impact of intensity of competition, decentralization and four organizational capabilities (market orientation, entrepreneurship, innovativeness and organizational learning) on the usage of SMA. The results of partial least squares (PLS) test appear to support the significant association between differentiation strategy and the two dimensions of SMA, the significant association between the four organizational capabilities collectively and SMA usage. But there is no significant association between some contextual variables (intensity of competition, decentralization and strategic role of accountant) and SMA usage. Despite that there is a positive association between strategic role of accountant and differentiation strategy, strategic role of accountant surprisingly shows a negative association with firm performance. In addition, SMA usage is found to be positively associated with firm performance, but the relationship is not significant. Further PLS test on large size companies, however, found a positive association between strategic role of accountant and SMA usage, and between SMA usage and firm performance. The mediating role of SMA usage on strategy-performance relationship is apparent in large size companies but not in small size companies. The qualitative information obtained from the post-survey interviews of six corporations reflected that most large corporations in Malaysia do apply contemporary management accounting techniques in supplementing the traditional management accounting such as standard costing and variance analysis. But the term „SMA‟ is not widely used in Malaysia. SMA techniques can be used interactively through regular meetings among managers. The companies interviewed also agree that there is a changing role of management accountants towards participation in strategic decision-making process and organizational learning, though there is a need for accountants to be more passionate and outward-looking in the manufacturing industry. This research contributes to the limited literature in SMA and role of accountants in strategic decision-making process, and bridging the gaps between management control and strategic management. Organizational capabilities (market orientation, entrepreneurship, innovativeness and organizational learning) collectively help the firms to enhance competitiveness and performance as well as impact the usage of SMA. Lastly, this study reaffirms the contingency theory that there is no universally appropriate management accounting system that applies equally well to all organizations in all circumstances. In this study, strategy and company size are important factors influencing the contingent outcome of SMA. Key words: Strategic Management Accounting, Management Control Systems, Organizational Capabilities, Management Accountants, Malaysia